2018
DOI: 10.21608/bvmj.2018.39583
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Role of Pyrethroids on Male Fertility and Seminal Profile of Rat

Abstract: A B S T R A C TA total number of 80 Wister male rats, 9 -wk. old were taken, weighed and divided into four experimental groups to investigate the effect of Deltamethrin (DLM) oral administration (0.87, 8.7 and 17.4 mg/kg B.W) for a period of 9 weeks on reproductive organs and fertility indices of Wister male rats. The results indicated that DLM caused a significant reduction in Testis weights, sperm count, motility and viability and fructose in semen. Also induced decreases in serum FSH, LH and Estradiol level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…These data are supported by the histological studies which revealed degeneration of the testicular and ovarian cells. These results are in parallel with Abdel-Maksoud et al (2018), Ghosh et al (2018) and Abd El-Hameed and Mahmoud (2020) who indicated that pyrethroids enhance suppression in male and female hormones. Testosterone is important to maintain both of structure and function of the male accessory sex gland.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These data are supported by the histological studies which revealed degeneration of the testicular and ovarian cells. These results are in parallel with Abdel-Maksoud et al (2018), Ghosh et al (2018) and Abd El-Hameed and Mahmoud (2020) who indicated that pyrethroids enhance suppression in male and female hormones. Testosterone is important to maintain both of structure and function of the male accessory sex gland.…”
Section: Discussionsupporting
confidence: 82%
“…It was reported that pyrethroids could affect ovulation causing atresia of follicles, decreasing follicular cells, oocytes and corpora lutea as well as inducing vesicular atrophy of the endometrial glands of mammals (Kotil and Yön, 2015;Marettova et al, 2017). Previous studies have indicated that several pyrethroids induce toxic impacts on the reproduction of mammals (Marettova et al, 2017;Abdel-Maksoud et al, 2018;Zhang et al, 2021;Zhong et al, 2021). Pyrethroids and their metabolites showed toxic effects on the endocrine system causing disturbances in the female hormones of mammals (Fei et al, 2010;Liu et al, 2011;Jurewicz et al, 2020).…”
Section: Introductionmentioning
confidence: 99%